Fricton knot tribioelectrochemical parameters under the influence of impulse modular current - Свирид, М.М. (Proceedings of National Aviation University (archive), 2010)
Conditions of donor element material transferring (material of auxiliary electrode) are studied in working solutions with high electroresistance under conditions of tribiolectrochemical influences on cathode surface (friction pair). Working parameters of tribiolectrochemical renewal process are defined in solutions of polyethylene glycol-400 under the influence of impulse modular current.